2019
DOI: 10.1039/c8sc05757e
|View full text |Cite
|
Sign up to set email alerts
|

An Al-doped SrTiO3photocatalyst maintaining sunlight-driven overall water splitting activity for over 1000 h of constant illumination

Abstract: The development of robust and efficient water splitting photocatalysts overcomes a long-standing barrier to sustainable large-scale solar hydrogen evolution systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 180 publications
(121 citation statements)
references
References 23 publications
2
110
0
Order By: Relevance
“…The result suggests that the degradation of the Rh 0.7 Cr 1.3 O 3 co‐catalyst is also progress beside the overall H 2 O splitting. According to the previous studies, the degradation of the Rh y Cr 2‐y O 3 co‐catalyst was reported to proceed by oxidizing Cr 3+ to Cr 6+ as chromate ion to dissolve in H 2 O. From the investigations in the previous study, under the oxidation process of H 2 O by photo‐generated holes, the degradation of the Rh 0.7 Cr 1.3 O 3 co‐catalyst also proceeds instead of production of O 2 .…”
Section: Influence Of Co‐catalysts To the Overall H2o Splitting Over mentioning
confidence: 95%
See 4 more Smart Citations
“…The result suggests that the degradation of the Rh 0.7 Cr 1.3 O 3 co‐catalyst is also progress beside the overall H 2 O splitting. According to the previous studies, the degradation of the Rh y Cr 2‐y O 3 co‐catalyst was reported to proceed by oxidizing Cr 3+ to Cr 6+ as chromate ion to dissolve in H 2 O. From the investigations in the previous study, under the oxidation process of H 2 O by photo‐generated holes, the degradation of the Rh 0.7 Cr 1.3 O 3 co‐catalyst also proceeds instead of production of O 2 .…”
Section: Influence Of Co‐catalysts To the Overall H2o Splitting Over mentioning
confidence: 95%
“…Recently, metal ion doped SrTiO 3 combined with a Rh y Cr 2‐y O 3 co‐catalyst was reported to show the excellent photocatalytic activity to the reaction. Particularly, Al ion doped SrTiO 3 prepared by the flux method exhibits extremely high photocatalytic activity under the irradiation of near‐UV region light that is containing the solar irradiation, where the apparent quantum yield is more than 50 % at 365 nm. A panel type reactor was made with using the photocatalyst and the overall H 2 O splitting was demonstrated under solar irradiation .…”
Section: Influence Of Co‐catalysts To the Overall H2o Splitting Over mentioning
confidence: 99%
See 3 more Smart Citations